Microstructure evolution and growth behavior of Cu/SAC105/Cu joints soldered by thermo-compression bonding. Issue 4 (2nd September 2019) - Guo, Mengjiao; Sun, F.; Yin, Zuozhu
Abstract : Purpose: This paper used a novel technique, which is thermo-compression bonding, and Sn-1.0Ag-0.5Cu solder to form a full intermetallic compound (IMC) Cu3 Sn joints (Cu/Cu3 Sn/Cu joints). The purpose of the study is to form high-melting-point IMC joints for high-temperature power electronics applications. The study also investigated the effect of temperature gradient on the microstructure evolution and the growth behavior of IMCs. Design/methodology/approach: In this paper, the thermo-compression bonding technique was used to form full Cu3 Sn joints. Findings: Experimental results indicated that full Cu/Cu3Sn/Cu solder joints with the thickness of about 5-6 µm are formed in a short time of 9.9 s and under a low pressure of 0.016 MPa at 450°C by thermo-compression bonding technique. During the bonding process, Cu6 Sn5 grew with common scallop-like shape at Cu/SAC105 interfaces, which was followed by the growth of Cu3 Sn with planar-like shape between Cu/Cu6Sn5 interfaces. Meanwhile, the morphology of Cu3 Sn transformed from a planar-like shape to wave-like shape until full IMCs solder joints were eventually formed during thermo-compression bonding process. Asymmetrical growth behavior of the interfacial IMCs was also clearly observed at both ends of the Cu/SAC105 (Sn-1.0Ag-0.5Cu)/Cu solder joints. Detailed reasons for the asymmetrical growth behavior of the interfacial IMCs during thermo-compression bonding process are given. The compound of Ag element causes a reduction in Cu dissolution rate from the IMC into the solder solution at the hot end, inhibiting the growth of IMCs at the cold end. Originality/value: This study used the thermo-compression bonding technique and Sn-1.0Ag-0.5Cu to form full Cu3 Sn joints.